Revascularization in "no option" patients with refractory angina: Frequency, etiology and outcomes. Issue 7 (5th August 2018) - Sharma, Rahul; Tradewell, Michael; Kohl, Louis P.; Garberich, Ross F; Traverse, Jay H.; Poulose, Anil; Brilakis, Emmanouil S; Arndt, Theresa; Henry, Timothy D
Abstract: Background: A significant proportion of patients with complex, advanced coronary artery disease have refractory angina (RA) despite maximal pharmacological therapy and are deemed suboptimal candidates for revascularization. These patients are frequently termed "no‐option" patients. However, despite this designation, many subsequently undergo coronary revascularization. We sought to determine the incidence, etiology and outcome of revascularization in "no‐option" patients. Methods and Results: We examined a comprehensive, prospective RA database to identify 342 of 1363 (25.1%) patients who subsequently underwent revascularization after a median interval of 2.2 years from the "no‐option" diagnosis. Coronary revascularization was achieved by percutaneous coronary intervention (PCI) (n = 274, 20.1%), coronary bypass graft surgery (n = 44, 3.2%) or both (n = 24, 1.8%). During a median follow‐up of 5.1 years, patients who underwent revascularization had lower annual mortality (2% vs. 4.4%, P  < .001). Detailed paired angiographic records were available for 181 PCI patients with a combined 302 lesions. Of these interventions, 48% were for a new lesion, 31% for an existing lesion and 21% for restenosis. The location was a native vessel in 77% and a bypass graft in 23%. Conclusions: The "no‐option" or non‐revascularizable designation is frequently based on angiography at a single time‐point. However, coronary artery disease is a progressive and dynamic process and new lesions often develop in such patients. Given the association between revascularization and better survival, careful consideration should be given to repeat revascularization in patients with refractory angina previously classified as "no‐option".